RECONSTRUCTION OF LEGAL LIABILITY OF REGISTRATION BY NOTARY FIDUCIARY BASED ON PP No. 21 of 2015 - Wieke Dewi Suryandari (UNISSULA, 2018)
Fiduciary term that has long been known in the Indonesian language. Similarly, the term is used in Act No. 42 of 1999 regarding Fiduciary. In the terminology of the Dutch term is often referred to in full, namely Fiduciare Eigendom Overdracht (FEO), namely the delivery of property rights in the trust. The methods used in this study, using juridical-empirics. Judicial approach used to analyze the various rules and regulations governing the fiduciary agreement and fiduciary While the English term is called Fiduciary Transfer of Ownership.Background onset of fiduciary institutions, as set out by the experts is because the statutory provisions governing the institution pand (pawn) contains many flaws, does not meet based on developments in its history, Fiduciary originated from an agreement that only is basedon trust. But over time in practice the necessary legal certainty to protect the interests of the parties and the needs of society.